Population Diversity of Campylobacter jejuni in Poultry and Its Dynamic of Contamination in Chicken Meat. (12th October 2015) - Marotta, Francesca; Garofolo, Giuliano; Di Donato, Guido; Aprea, Giuseppe; Platone, Ilenia; Cianciavicchia, Silvia; Alessiani, Alessandra; Di Giannatale, Elisabetta
Abstract : This study aimed to analyse the diversity of the Campylobacter jejuni population in broilers and to evaluate the major source of contamination in poultry meat. Eight rearing cycles over one year provided samples from three different broiler farms processed at the same slaughterhouse. A total of 707 C. jejuni were isolated from cloacal swabs before slaughter and from the breast skin of carcasses after slaughter and after chilling. All suspected Campylobacter colonies were identified with PCR assays and C. jejuni was genotyped by sequence analysis of the flaA short variable region (SVR) and by pulsed-field gel electrophoresis (PFGE) using SmaI enzyme. Phenotypic antibiotic resistance profiles were also assayed using minimal inhibitory concentration (MIC). The flocks carried many major C. jejuni clones possibly carrying over the rearing cycles, but cross contamination between farms may happen. Many isolates were resistant to fluoroquinolones, raising an issue of high public concern. Specific Campylobacter populations could be harboured within each poultry farm, with the ability to contaminate chickens during each new cycle. Thus, although biosecurity measures are applied, with a persistent source of contamination, they cannot be efficient. The role of the environment needs further investigation to better address strategies to control Campylobacter .